Thalassemia Major and Associated Psychosocial Problems: A Narrative Review - Hazel Şahin Tarım; Fatma Öz (Iranian Journal of Public Health, 2022)
Thalassemia is an inherited disease that causes the production of damaged hemoglobin chains. Patients are diagnosed with thalassemia major due to major clinical signs and deep anemia. This study aimed to examine the major thalassemia and psychosocial aspect of it, which is such an important issue, to serve as a roadmap for better handling these patients and to contribute to the literature. The method used in this study was narrative review. A literature review was conducted by searching the materials published in databases including Web of Science, PubMed, Scopus, and Google Scholar search engine from 2001 to 2020. Besides WHO website was searched. Thalassemia major damages the heart, liver, lungs and endocrine organs due to anemia and iron accumulation. In addition, the patient may experience mental and social problems due to the congenital nature of the disease and its lifelong duration. The psychosocial problems and treatment burdens of thalassemia patients are very high. There are many studies about the prevalence and physical consequences of thalassemia. However, there are not enough articles and researches describing the psychosocial effects of thalassemia on patients and what can be done about these effects. For this reason, this paper focuses on the process of thalassemia and the psychosocial problems it creates to contribute to the literature and to be a roadmap for better handling these patients.